Cosegregation of a novel mutation in the sixth transmembrane segment of the luteinizing/choriogonadotropin hormone receptor with two Brazilian siblings with severe testotoxicosis. (3rd April 2017) - Siviero-Miachon, Adriana A.; Kizys, Marina M. L.; Ribeiro, Manuela M.; Garcia, Fabiola Esgrignoli; Spinola-Castro, Angela M.; Dias da Silva, Magnus R.
ABSTRACT: Purpose : Testotoxicosis is an autosomal dominant form of gonadotropin-independent precocious puberty caused by heterozygous constitutively activating mutations of the luteinizing hormone/choriogonadotropin receptor (LHCGR) gene. The aim of this study was to describe two Brazilian siblings with testotoxicosis, to confirm the molecular diagnosis, and to perform an in silico analysis of a novel mutation in the hot spot of the LHCGR gene.Materials and methods : Molecular analysis of the mutation on the LHCGR gene was performed by direct Sanger sequencing, followed by an in silico analysis using HOPE bioinformatics tool to predict a functional defect of the mutant.Results : Both patients presented with gonadotropin-independent precocious puberty before the age of four years. Genetic analysis revealed a novel non-maternally inherited p.Asp578Val mutation of the LHCGR gene. An in silico analysis showed that the p.Asp578Val mutation disturbed amino acid physicochemical features regarding its size, charge, and hydrophobicity value.Conclusions : Clinical and hormonal profile of the siblings here evaluated was not different while compared to those patients previously described. An in silico mutation analysis reinforced the causative role of recurrent activating mutations in the intracellular loop and transmembrane helices of the LHCGR. The segregation of this mutation with the offsprings' phenotype indicated that it is causative.